PENGATURAN PERADILAN ADAT DALAM AWIG-AWIG DESA PAKRAMAN: STUDI PENDAHULUAN TENTANG EKSISTENSI PERADILAN ADAT DALAM KESATUAN MASYARAKAT HUKUM ADAT DESA PAKRAMAN - I Ketut Sudantra (University of Udayana, 2014)
This study aims to determine the regulation on customary justice in the traditionalrules of awig-awig of pakraman village, the rules made by the customarycommunity unit of Pakraman village in Bali. This study focused on structure,competency, mechanism, and principle of customary justice. The result shows thatstructure and competency of customary justice have been regulated clearly onawig-awig of pakraman village, but the mechanism of customary justice doesn’tregulated clearly. Awig-awig of desa pakraman only regulates initial mechanism,namely the process of filing a case, but does not regulate mechanisms after thecase was subsequently processed by the customary justice. It can be identifiedsome principles in awig awig of pakraman village to be a guidance for thecustomary courts in resolving cases that occur on it’s jurisdiction